Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Make a Match Terhadap Hasil Belajar Siswa Kelas X Pada Mata Pelajaran Pendidikan Agama Islam di SMAN 1 Sungai Puar - Laila Rahima; Zulfani Sesmiarni; Charles Charles; Salmi Wati (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This research is a quantitative research with experimental type and quasi-experimental research design in the form of nonequivalent control group design. Sampling using the Nonprobability Sampling technique with purposive sampling type, the research sample amounted to 42 people, with a population of 131 people. The instrument is an objective test in the form of multiple choice. Data analysis with descriptive statistics, then the analysis requirements test consists of normality test and homogeneity test. And for hypothesis testing using t-test (t-test). Based on the initial test or pretest conducted in the experimental class, an average of 55.5 was obtained. While in the control class, obtained an average of 63.18. After being given a pretest to both classes, then the make a match learning model was carried out in the experimental class and conventional learning in the control class. After that, both classes were given a final test or posttest, the experimental class obtained an average of 86.25 with the highest score of 100 and the lowest score of 65, while the control class obtained an average of 82.5 with the highest score of 100 and the lowest score of 50. Furthermore, The analysis prerequisite test was carried out, namely the normality and homogeneity test of posttest scores with the results of the data being normal and homogeneous. Thus, it can be concluded that there is a significant effect of the application of the make a match learning model on the learning outcomes of class X students in PAI subjects at SMAN 1 Sungai Puar